2016
DOI: 10.1002/dc.23613
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human papillomavirus, Epstein‐Barr virus, and cytomegalovirus in fine needle aspirates from lung carcinoma: A case–control study with review of literature

Abstract: We conclude that fine needle aspirates can serve as reliable sample for PCR based detection of viruses. A significantly higher prevalence of HPV in lung cancer and a significant association with SCC was observed, thereby, indicating a positive link between HPV and etiopathogenesis of lung carcinoma. Diagn. Cytopathol. 2016;44:987-993. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
(106 reference statements)
1
11
0
Order By: Relevance
“…Of interest, a number of authors have reported findings similar to ours or even higher HPV positivity rates in lung cancer tissues: 21% in Italy, 30% in Finland, 49% in Norway, 69% and 19% in Greece . In addition, some recent publications have indicated a positive link between HPV and etiopathogenesis of lung carcinoma, supporting the present findings . However, others have failed to identify such a causative link .…”
Section: Discussionsupporting
confidence: 87%
“…Of interest, a number of authors have reported findings similar to ours or even higher HPV positivity rates in lung cancer tissues: 21% in Italy, 30% in Finland, 49% in Norway, 69% and 19% in Greece . In addition, some recent publications have indicated a positive link between HPV and etiopathogenesis of lung carcinoma, supporting the present findings . However, others have failed to identify such a causative link .…”
Section: Discussionsupporting
confidence: 87%
“…HPV infection is a strongly associated and numerous studies have shown that infection with HR-HPV genotypes represents an associated factor for its development ( Gillison et al, 2000 ; Vokes, Agrawal & Seiwert, 2015 ). In addition, other viruses with oncogenic potential such as EBV and MCPV that have been detected in the nasopharyngeal tract, tonsils, salivary glands, and lungs may play an important role ( Baez et al, 2015 ; Pezzuto et al, 2015 ; Gupta et al, 2016 ). At present, there are insufficient reports describing the epidemiology of viral coinfections in tumors of the larynx, so studies in this regard could contribute to clarify their association with the carcinogenic progression and to facilitate preventive strategies ( Bansal, Singh & Rai, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The low rate of HPV detection in our patient cohort was expected because HPV-positive HNSCC does not tend to form distant metastases and primary lung SCC also tends to be HPV-negative. 9,10,38 By contrast, the observation that correctly identifying the lung tumor origin depended on mutational profiling of TP53 exons other than 5 to 8 in 6 of 32 cases (19%) puts the common limitation of TP53 mutation analysis to exons 5 to 8 in question and shows that detection of TP53 mutations should comprise all coding exons in order to maximize the sensitivity of the assay. 35 Remarkably, a comparison of lung tumor origin diagnoses made with or without molecular genetic data revealed that 16 of 29 patients (55%) for whom a clear diagnosis could be made by HPV typing and mutational profiling had received an incorrect diagnosis of the lung tumor origin when this diagnosis was based on clinical and morphological data alone.…”
Section: Daher Et Almentioning
confidence: 99%